PENGARUH BRAND IMAGE DAN TRUST TERHADAP LOYALITAS KONSUMEN DENGAN VALUE PRODUCT SEBAGAI MODERATING (STUDI PADA UMKM BANDENG PRESTO DI KOTA SEMARANG) - Agus Budi Purwanto; Untung Widodo (STIE Pelita Nusantara Semarang, 2019)
The background of this research is the weaker brand image of the results of SMEs presto milkfish products, and the weak consumer confidence in SMEs presto milkfish products in the city of Semarang. In general, this study aims to determine the effect of brand image and trust on consumer loyalty where the product value as a moderating variable. In particular, this study aims to improve the competitiveness of milkfish presto products. The variables in this study consisted of four variables, namely brand image and trust became independent variables while consumer loyalty became the dependent variable. Then the product value is a moderating variable. Research data collection techniques by distributing questionnaires to consumers of presto milk products in the city of Semarang are systematically arranged with several easy-to-understand answer choices. The distribution of questionnaires was carried out during the period May - August 2017, with a sample of 125 people. Then the data collected through the questionnaire was tested for validity and reliability. Hypothesis testing uses multiple regression analysis and MRA (Moderated Regression Analysis. To get the BLUES regression results (best linear unbiased estimated), the classical assumption test was previously carried out. This research is motivated by the weak brand image of milkfish presto products, as well as the weak consumer confidence in presto milkfish products in Semarang City. In general, this study aims to determine the effect of brand image and trust on consumer loyalty where the product value as a moderating variable. In particular, this study aims to improve the competitiveness of milkfish presto products. The variables in this study consisted of four variables, namely brand image and trust became independent variables while consumer loyalty became the dependent variable. Then the product value is a moderating variable. Research data collection techniques by distributing questionnaires to consumers of presto milk products in the city of Semarang are systematically arranged with several easy-to-understand answer choices. The distribution of questionnaires was carried out during the period May - August 2018, with a sample of 125 people. Then the data collected through the questionnaire was tested for validity and reliability. Hypothesis testing uses multiple regression analysis and MRA (Moderated Regression Analysis. To get BLUES regression results (best linear unbiased estimated), classical assumptions have been tested before. The results show that brand image has a positive and significant effect on loyalty, trusts have a positive effect and significant to loyalty, brand image has a stronger influence on loyalty when driven by product value, trust has a stronger influence on loyalty when driven by value products.